FXR promotes clear cell renal cell carcinoma carcinogenesis via MMP-7-regulated EMT pathway - Jiachen Liu; Shiyu Huang; Yanguang Hou; Shujie Fu; Lei Wang; Juncheng Hu; Cheng Liu; Xiuheng Liu (Scientific Reports)
Abstract Renal cell carcinoma (RCC) ranks as a prevalent malignant neoplasm, with clear cell renal cell carcinoma (ccRCC, also known as KIRC) accounting for approximately 75% of all RCC cases. The farnesoid X receptor (FXR, encoded by NR1H4), functioning as a nuclear receptor, plays a crucial role in regulating gene transcription. Although the involvement of FXR in tumors of the digestive system and in acute kidney injury has been extensively studied, its specific role in the pathogenesis of ccRCC has yet to be thoroughly investigated. Consequently, the objective of our current investigation is to uncover the functional roles of FXR in ccRCC. In this study, plasmids for the overexpression of FXR were constructed, and small interfering RNA (siRNA) constructs were designed. Dual-luciferase reporter assays confirmed a direct binding interaction between FXR and the promoter of the matrix metalloproteinase 7 (MMP-7) gene. Additionally, a mouse xenograft model elucidated the regulatory effect of FXR on MMP-7 in the context of tumor growth. This study elucidates how FXR regulates the promotion of ccRCC through the MMP-7-mediated EMT pathway. Interestingly, FXR is typically regarded as a tumor suppressor gene that affects gastrointestinal tumors, providing a potential new therapeutic direction for ccRCC.